Functional Conductive Hydrogels for Bioelectronics - Fu, Fanfan; Wang, Jilei; Zeng, Hongbo; Yu, Jing (ACS materials letters, 2020)
Conductive hydrogels are widely used in various applications, such as artificial skin, flexible and implantable bioelectronics, and tissue engineering. However, it is still a challenge to formulate hydrogels with high electrical conductivity without compromising their physicochemical properties (e.g., toughness, stretchability, and biocompatibility). Additionally, incorporating other functions, such as self-healing, shape memory, and wet adhesion, into conductive hydrogels is critical to many practical applications of hydrogel bioelectronics. In this Review, we highlight recent progress in the development of functional conductive hydrogels. We, then, discuss the potential applications and challenges faced by conductive hydrogels in the areas of wearable/implantable electronics and cell/tissue engineering. Conductive hydrogel can serve as an important building block for bioelectronic devices in personalized healthcare and other bioengineering areas.